2020
DOI: 10.1038/s41389-020-00279-7
|View full text |Cite
|
Sign up to set email alerts
|

Notch3 contributes to T-cell leukemia growth via regulation of the unfolded protein response

Abstract: Unfolded protein response (UPR) is a conserved adaptive response that tries to restore protein homeostasis after endoplasmic reticulum (ER) stress. Recent studies highlighted the role of UPR in acute leukemias and UPR targeting has been suggested as a therapeutic approach. Aberrant Notch signaling is a common feature of T-cell acute lymphoblastic leukemia (T-ALL), as downregulation of Notch activity negatively affects T-ALL cell survival, leading to the employment of Notch inhibitors in T-ALL therapy. Here we … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 65 publications
1
10
0
Order By: Relevance
“…First, we used the Notch1-activated KE-37 cell line, being Notch1 a frequent target of oncogenic gain-of-function mutations in T-ALL patients ( 11 ). Interestingly, KE-37 cells are GSI resistant and Notch3 negative ( 42 ) and express intracellular IL-6 ( Supplementary Figure S5A ). The harvested PBMCs/KE-37 coculture samples reveal a significant increase of CD14 + HLA-DR low/neg “putative” MDSCs, both in percentages ( Figures 7A, B , left panel) and absolute numbers ( Figure 7B , right panel), when compared with samples of autologous PBMCs cultured alone.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…First, we used the Notch1-activated KE-37 cell line, being Notch1 a frequent target of oncogenic gain-of-function mutations in T-ALL patients ( 11 ). Interestingly, KE-37 cells are GSI resistant and Notch3 negative ( 42 ) and express intracellular IL-6 ( Supplementary Figure S5A ). The harvested PBMCs/KE-37 coculture samples reveal a significant increase of CD14 + HLA-DR low/neg “putative” MDSCs, both in percentages ( Figures 7A, B , left panel) and absolute numbers ( Figure 7B , right panel), when compared with samples of autologous PBMCs cultured alone.…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, we performed experiments above with the Notch3-activated T-ALL cell line, TALL-1 ( 31 ) that is IL-6 + ( Supplementary Figure S5A ) and Notch1-negative ( 42 ). TALL-1 cells promote the induction of suppressive MDSCs ( Supplementary Figures S5B–D ) that is inhibited by exposure to GSIs or anti-IL-6 antibodies ( Supplementary Figures S5E, F , respectively).…”
Section: Resultsmentioning
confidence: 99%
“…Leukemia is characterized by the accumulation of gene mutations and chromosomal translocations that the encoding proteins are frequently prone to misfolding ( 23 , 44 , 45 ). It has been reported that sustained UPR exists in multiple leukemia types and plays a vital role in disease progression and therapeutic resistance ( 19 , 20 , 46 48 ). Thus, targeting ER stress and UPR mechanisms represents attractive therapeutic options to the leukemia treatment ( 49 53 ).…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, the natural occurring phenolic compound juglone (5-hydroxy-1,4-naphthoquinone) had anti-Notch3 activities both in in vitro and in vivo leukemia settings, thus suggesting juglonebased therapies as potential approaches for the treatment of Notch3-dependent T-ALL [346].…”
Section: Natural Compounds As Notch Signaling Modulatorsmentioning
confidence: 99%